(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article examines ways to reduce tax debt in CIS countries and suggests potential solutions that can be applied in other countries. The article examines the identification and improvement of tax debt and its impact on the economy, and makes scientific and practical conclusions and proposals for its application in our country.